Efectos en la morfometría de pollos cuello desnudo en pastoreo, alimentados con harina de hoja de plátano (musa paradisiaca l) incluida en el balanceado - Almeida Mora, Melissa Magdalena (2016)
In the Experimental Farm "La Maria" at the Faculty of Animal Science, State Technical University of Quevedo (UTEQ) in the Poultry Program, located in the km 7 via QuevedoEl Empalme, Canton Mocache, this work was performed " Effects manometry naked neck chickens grazing, fed flour banana leaves (Musa paradisiaca L.) included in the balanced ", lasting sixty days. The parameters were morphometric measurements, organoleptic analysis channel (breast), for which, 36 male birds and 18 female 18 six replicates, two birds per replicates were used. The treatments were: T0 = Control (balanced more flour without restriction); T1 = more balanced banana leaf meal with 25% restriction; T2 = more balanced banana leaf meal with 50% restriction; complete block design at random (DBCA) was used. The results of this work were subjected to analysis of variance (ANOVA) for comparisons of treatment means the Tukey test (P <0.05) was used. In absolute and relative carcass of males and females (live weight, carcass, breast, leg, thigh, leg and neck) had significant differences between treatments (P <0.05), weights also were no differences in the viscera full of chickens proventricle male and blind, in empty viscera, in gizzard, proventriculus, blind and small intestine and cocks females only blind and small intestine empty viscera, when food 25 and 50% weight decreases indicators is restricted. In the accessory glands had differences in the indicators heart, liver and glass in males and in females only in heart and liver. The lengths (cm) obtained differences in breast, proventriculus, small intestine, blind, in male broilers and females only and blind scruff